Residents’ views on intangible cultural heritage and the possibility of improving the tourist offer - Gržinić, Jasmina; Bertoša, Slaven; Podrug, Iva (Oeconomica Jadertina, 2025)
Oral traditions should be a key factor in cultural creativity, identity development, and sustainable tourism. This work contributes to a deeper understanding of intangible cultural heritage in the role of building cultural identity. At the same time, it reminds us of their importance as a possible foundation of intangible heritage that can connect the past with the future. The subject of the research is the role and significance of Dalmatian oral traditions as a form of intangible cultural heritage. Through the analysis of intangible heritage, symbolism, and the transmission process within the community, the importance of oral traditions as a key factor in preserving the community's cultural identity is highlighted. The emphasis is on the role of intangible culture in modern society, as well as on the challenges, protection, and reinterpretation in the context of tourism. The work is based on a survey method directed to the residents of destinations through an online questionnaire conducted in May 2025. The results confirm the connection between the local population and oral tradition, with an emphasis on storytelling. It was noted that the majority of respondents believe that folk traditions should have an important role in education and cultural programs. At the same time, the role of tourist boards in activating traditional actors and factors important for the preservation of cultural traditions was recognized. The results indicate that traditions are still represented in the collective consciousness of the community. The need for a multi-layered approach to the valorization of oral traditions through education, state and local governments, media, cultural institutions, and the local community in the process of transmitting traditions to younger generations was identified. Monitoring the attitudes of the community through longitudinal studies in order to improve the tourist offer through the diversification of the tourist product and the development of year-round tourism. The research limitations are in the small sample size. It should be a subject of interest for future researchers of regional traditions.
Keywords: intangible cultural heritage, oral traditions, local population, protection, sustainability